Thermogenic Capacity of Human Supraclavicular Brown Fat and Cold-Stimulated Brain Glucose Metabolism - U-Din Mueez; Rebelos Eleni; Saari Teemu; Niemi Tarja; Kuellmer Katharina; Eskola Olli; Fromme Tobias; Rajander Johan; Taittonen Markku; Klingenspor Martin; Nuutila Pirjo; Nummenmaa Lauri; et al. (MDPI, 2025)
Human brain metabolism is susceptible to temperature changes. It has been suggested that the supraclavicular brown adipose tissue (BAT) protects the brain from these fluctuations by regulating heat production through the presence of uncoupling protein 1 (UCP-1). It remains unsolved whether inter-individual variation in the expression of UCP-1, which represents the thermogenic capacity of the supraclavicular BAT, is linked with brain metabolism during cold stress. Ten healthy human participants underwent F-18-FDG PET scanning of the brain under cold stimulus to determine brain glucose uptake (BGU). On a separate day, an excision biopsy of the supraclavicular fat-the fat proximal to the carotid arteries supplying the brain with warm blood-was performed to determine the mRNA expression of the thermogenic protein UCP-1. Expression of UCP-1 in supraclavicular BAT was directly related to the whole brain glucose uptake rate determined under cold stimulation (rho = 0.71, p = 0.03). In sub-compartmental brain analysis, UCP-1 expression in supraclavicular BAT was directly related to cold-stimulated glucose uptake rates in the hypothalamus, medulla, midbrain, limbic system, frontal lobe, occipital lobe, and parietal lobe (all rho >= 0.67, p < 0.05). These relationships were independent of body mass index and age. When analysing gene expressions of BAT secretome, we found a positive correlation between cold-stimulated BGU and DIO2. These findings provide evidence of functional links between brain metabolism under cold stimulation and UCP-1 and DIO2 expressions in BAT in humans. More research is needed to evaluate the importance of these findings in clinical outcomes, for instance, in examining the supporting role of BAT in cognitive functions under cold stress.